Shifting into Action: from Data Segmentation to Equitable Interoperability for Adolescents (and Everyone Else) - Sarabu, Chethan; Sharko, Marianne; Petersen, Carolyn; Galvin, Hannah (Applied Clinical Informatics, 2023)
Background Technological improvements and, subsequently, the federal 21st Century Cures Act have resulted in increased access to and interoperability of electronic protected health information (ePHI). These not only have many benefits, but also have created unique challenges for privacy and confidentiality for adolescent patients. The inability to granularly protect sensitive data and a lack of standards have resulted in limited confidentiality protection and inequitable access to health information.Objectives This study aimed to understand the challenges to safe, equitable access, and interoperability of ePHI for adolescents and to identify strategies that have been developed, ongoing needs, and work in progress.Methods Shift, a national task force formalized in 2020, is a group of more than 200 expert stakeholder members working to improve functionality to standardize efforts to granularly identify and protect sensitive ePHI to promote equitable interoperability.Results Shift has created high-priority clinical use cases and organized challenges into the areas of Standards and Terminology; Usability and Implementation; and Ethics, Legal, and Policy.Conclusion Current technical standards and value sets of terminology for sensitive data have been immature and inconsistent. Shift, a national diverse working group of stakeholders, is addressing challenges inherent in the protection of privacy and confidentiality for adolescent patients. The diversity of expertise and perspectives has been essential to identify and address these challenges.
Keywords: interoperability; privacy; confidentiality; standards; implementation; data segmentation; DS4P; adolescent